Narcolepsy and H1N1 vaccine (2014)
Narcolepsy is a sleep disorder described as excessive sleepiness with abnormal sleep pattern characterized by uncontrollable rapid eye movement (REM) attacks, in which the preceding non-REM stage is absent. These attacks can occur at any time of the day and can be accompanied by a loss of muscle tone. A plethora of data indicates that narcolepsy is caused by a lack of orexin, an important neurotransmitter involved in the regulation of the sleep cycle. Normal levels of orexin are needed for the correct function of different processes in the body, including feeding, cardiovascular regulation, emotions, and locomotion. The pathogenesis of narcolepsy has been debated for many years. It has been suggested that genetic, autoimmune, or infectious processes may be involved. An important aspect in the etiology of narcolepsy is some reports demonstrating a correlation between its onset and infections or H1N1 vaccination. © 2015 Wiley-Blackwell.